Estudo Estratigráfico e Paleontológico do Jurássico do Algarve Ocidental - Rocha, R. B. (2008)
Algarve Province, Southern Portugal, corresponds in part to a meso-cenozoic basin running along the coast from Cabo S. Vicente to beyond Spanish border. Structurally it is a big monocline plunging southwards much deformed mainly by two East-West longitudinal flexures. Lithostratigraphical and chronostratigraphical studies dealt specially with Jurassic formations. This and the geological mapping of the post-Hercynian sedimentary formations allow us to define the following units: Triassic-Lower Liassic Arenitos de Silves (Silves sandstones sensu P. Choffat, pro parte) - At their base the Silves sandstones (0-150m) are represented mainly by cross-bedded red sandstones. This unit is Upper Triassic (Keuper) in age, on the evidence of some Brachiopoda. Complexo margo-carbonatado de Silves (Silves marl-limestone complex=Silves sandstones sensu P. Choffat, pro parte) (80-200m) overlies the preceding, it may be reported to the Upper Triassic-Hettangian. It consists of a thick pelite-marl-dolomite-limestone series with many intercalations of greenstones. Since no fossils were found it is not possible to conclude whether it is still Hettangian or if it does correspond, in the whole or in part, already to the Sinemurian. Liassic Dolomitos e calcários dolomíticos de Espiche (Espiche dolomite-rocks and dolomitic-limestones) - The usually massive and finely crystalline or saccharoidal dolomites and dolomitic-limestones are the toughest strata of the Algarve margin giving rise to several hills. Its thickness attains in certain points 60 metres at least. Based on geometry and on lithological similarities with the carbonated complex of the northern basin of Tagus river (Peniche, São Pedro de Muel, Quiaios), this formation can be accepted as Sinemurian in age. As it happens with the carbonated complex, here also the first dolomite beds are non-isochronal throughout the region; upper time-limit of the dolomitic facies is either Lower Carixian, Lower Toarcian or even Lower Dogger. The dolomitization is secondary but not much later than sedimentation. However, between Cabo S. Vicente-Vila do Bispo there is evidence of an even later secondary dolomitization related to the regional fault complex. Calcário dolomítico com nódulos de silex da praia de Belixe (Belixe beach dolomitic-limestone with silex nodules) (50-55m) - Ascribed to Lower or Middle Carixian on the basis of Platypleuroceras sp., Metaderoceras sp. nov. and M. gr. Venarense. Calcário cristalino compacto com Protogrammoceras, Fuciniceras e ? Argutarpites de Belixe (Belixe compact crystalline limestone with Protogrammoceras, Fuciniceras and ? Argutarpites) (30m) - Ascribed to Lower Domerian. Middle and Upper Domerian are indicated but by a single specimen of ? Argutarpites. Calcários margosos e margas com Dactylioceras semicelatum e Harpoceratídeos de Armação Nova (Armação Nova marly limestones and marls with D. semicelatum and Harpoceratidae) (25m) -Ascribed to Lower Toarcian. Middle and Upper Toarcian formations are not known in the Algarve. Dogger Calcários oolíticos, c. corálicos, c. pisolíticos, c. calciclásticos, c. dolomíticos e dolomitos de Almadena (Almadena oolitic-limestones, coral-reef-limestones, pisolite-limestones, limeclastic-limestones, dolomitic-limestones and dolomite-rocks) (more than 50 metres), with lagoonal facies. Ascribed to Aalenian-Bathonian-? Callovian. Margas acinzentadas e calcários detríticos com Zoophycos da praia de Mareta (Mareta beach greyish marls and detritical limestones with Zoophycos) (40m) - Pelagic transreef facies with Upper Bajocian and Bathonian ammonites. Calcários margosos e margas da praia de Mareta (Mareta beach pelagic marly-limestones and marls) (110m) - Ascribed to the Callovian on its ammonites. Malm Near Cabo S. Vicente and Sagres the first Upper Jurassic level consists of a yellowish-brown nodular, compact, locally phosphated and ferruginous, sometimes conglomeratic, marly limestone (0,35-1,50m) containing a rich macrofauna, which includes: 1) Callovian forms unknown at Lower Oxfordian; 2) Upper Callovian forms that still survived in Lower and Middle Oxfordian; 3) Lower Oxfordian forms (Mariae and Cordatum Zones); 4) Lower and Middle Oxfordian forms (Mariae to Plicatilis Zone); 5) Middle Oxfordian forms (plicatilis Zone), and some ones appearing in Middle Oxfordian. This condensed deposit is therefore dated from Middle Oxfordian (Plicatilis Zone). The other Upper Jurassic lithostratigraphical units were also mapped but their detailed study is not presented in this work. Correlations between lithostratigraphical and chronostratigraphical scales from P. Choffat, J. Pratsch, C. Palain and from the author are stated. Further correlations are attempted between zonc scales of Carixian-Lower Toarcian and Upper Bajocian-Middle Oxfordian of France, Spain (Asturias, Iberian and Betic Chains), Argel (Orania) and Portugal (northern Tagus basin and Algarve). The study of pyritous fossil assemblages common in Upper Bathonian-Lower Callovian marly levels of the praia da Mareta seems to suggest that these sediments were deposited in a bay or in an almost closed coastal re-entrance virtually without deep water circulation. Although such conditions may occur at any depth one may suppose that these ones actually correspond to an infralittoral neritic environment. The thaphocoenosis collected there are almost entirely composed of nektonic (ammonites, Belemnites) and planktonic (Bositra) faunas. The sedentary (crinoids, brachiopods) or free (sea-urchins, gastropods) epibenthonic forms are very scarce; endobenthonic forms are not known. The palaeontological study of all Nautiloids and Ammonoids of the Liassic and Dogger is presented (except Kosmoceratidae and Perisphinctaceae). Among the thirty one taxa dealt with, one is new (Metaderoceras sp. nov.) and the great majority of the others has been identified for the first time in Algarve. Some others have never been reported before in Portuguese formations. The evolution, during Jurassic times, of the sedimentary basins of the Portuguese plate margin is described. The absence of Cephalopods in the very extensive marly and dolomitic limestones, partly marine, suggests that, during Lower Liassic, palaeogeography underwent no great changes. Dolomitic-limestone with silex nodules from Cabo S. Vicente contain the first ammonites recorded at the base of the Middle Liassic. This facies, although very common in Tethys, is unknown north of the Tagus. The faunal assemblage has a mediterranean to submediterranean character. Comparisons between faunal assemblage" from Algarve with the ones known north of the Tagus show that communications between Boreal Europe and Tethys, virtually non-existent during Lower and Middle Carixian, became very easy during Lower Domerian. In earlier Pliensbachian times two distinct seas were adjacent to the Iberian plate. One, an epicontinental sea with a tethyan fauna, extended southwards from the Meseta margin. Another, was a boreal sea; during its transgressive episodes boreal faunas attained into the basin north of the Tagus. During Middle Carixian and Lower Domerian, owing to simultaneous transgressions, these two seas joined together allowing faunal exchanges along the epicontinental areas which limited the emerging hercynian chains belts. During Liassic, the Algarve belonged undoubtedly to the tethyan submediterranean province. The area north of the Tagus, on the contrary, was a complex realm where subboreal and tethyan affinities alternatively prevailed. In the Algarve the first Middle Jurassic deposits do frequently show lateral thickness reductions as well as unconformities contemporaneous with other generalized disturbances on the sedimentation processes in other parts of Europe. By this time, near Sagres, a barrier reef developed separating lagoonal or ante-reef facies from the transreef pelagic zone. The presence of tethyan fauna, the abundance of Phylloceratidae and the absence of boreal forms allow us to consider the Algarve basin as a submediterranean province. The presence of Callovian pelagic fossiliferous formations in the Loulé area shows that during Middle Jurassic the marl-limestone transreef sedimentation was not confined to the western Algarve. They would extend eastwards where they only can be seen in the core of some anticlines. This is due to the progressive sinking of the meso-cenozoic formations as we proceed towards the South of the Sagres-Algoz-Querença flexure. In the whole of the Peninsule, and as for the Middle Callovian, an important regression can be clearly recognized on the evidence of an erosion surface which strikes obliquely the Middle and Upper Callovian strata. The geographic boundaries of the different faunal provinces are not changed by the presence of many Kosmoceratidae in the phosphate nodules since they are but a minority in comparison with the tethyan forms. An abstract model can be constructed showing that in Western Europe the Kosmoceratidae may have migrated South and westwards through a channel of the sea that linked Paris basin to Poitou and Aquitaine. By migrating between the Iberian meseta and the Armorican massif this fauna reached northern Tagus basin at the beginning of Upper Callovian (Athleta Zone); this south and southwest bound migration would have proceeded, allowing such forms to reach Algarve basin only in latest Callovian times (Lamberti Zone). This migration means that during Middle Jurassic a widely spread North Atlantic sea would exist, flooding the western part of Portugal up to the Poitou.